EXPERIMENTAL STUDY ON GREEN DRILLING NICKEL-BASE SUPERALLOY WITH CARBIDE BIT (MT) - LI Hui; GAO Feng; LI Yan (Jixie qiangdu)
The carbide bit YG10 green drilled nickel-base superalloy GH4169 through dry drilling, air cooling and LCO2 cooling to explore the drilling performance and wear mechanism of nickel-base superalloy, with the purpose of improving the bit life. According to the analysis of bit life, drilling force, drilling temperature, drill wear morphology and machined surface roughness under different cutting conditions, both air cooling and LCO2 cooling can improve cutting conditions, reduce drilling force and drilling temperature, and prolong bit life. Air cooling and LCO2 cooling can increase cutting life by 33% and 2.33 times, respectively. It has a high requirement on the working condition when the carbide bit drills nickel-base superalloy. The main failure mode is chipping or even broken edge in inappropriate working conditions, and the main failure mode is adhesive wear in appropriate working conditions.